Structural design and analysis of a picking robot arm using parallel grippers - Fengfeng Wang; Yechen Fan (Advances in Mechanical Engineering)
The development of a versatile and reliable robotic arm for agricultural picking is essential for modern farming. This study presents the design of a picking robotic arm inspired by bionics principles. The end-effector features a parallel gripper structure to efficiently pick crops of various shapes and sizes, with finite element simulations confirming its structural rationality. The gripping force is measured by an LDTI-028K PVDF piezoelectric thin-film sensor, adjustable within a crop-safe range to prevent damage. Additionally, a new signal conditioning circuit is proposed to improve the signal-to-noise ratio by amplifying the sensor’s output signal and minimizing noise, addressing the relatively low surface charge produced by the PVDF film under external pressure. Adams simulation analyses show that the end-effector is highly adaptable. Furthermore, picking experiments demonstrate that the robotic arm can reduce costs and lower the attrition rate by approximately 23.2 ± 5% compared to manual picking, while also exhibiting high reliability and stability.